Customized birthweight standard for a Polish population - Anna Kajdy; Oliver Hugh; Jan Modzelewski; Michał Rabijewski; Andre Francis; Jason Gardosi (Archives of Medical Science)
Introduction There is a growing body of evidence supporting the role of customized growth charts in improving detection of fetal growth restriction (FGR) and decreasing false positive diagnoses. The aim of the study is to produce a customised birthweight standard for Poland.